Global trends and future predictions of pancreatic cancer incidence and mortality from 1990 to 2030: A comparative analysis of China, Korea, Japan, and the USA - Kun Huang; Xiang Lan; Zhu Chen; Heng Xiao; Shunhu Jia; Chenyou Du (PLoS ONE, 2025)
Background Pancreatic cancer is a leading cause of cancer-related deaths globally, with rapidly increasing incidence and mortality rates in several regions. This study provides a comparative analysis of pancreatic cancer trends in China, Korea, Japan, and the USA, and projects these trends through 2030. Methods Data from the Global Burden of Disease (GBD) study were used to examine trends in age-standardized incidence rates (ASIR), age-standardized mortality rates (ASMR), and disability-adjusted life years (DALYs) from 1990 to 2020. Joinpoint regression and age-period cohort (APC) models were employed to assess temporal trends. Future predictions of ASIR, ASMR, and DALYs were generated using predictive modeling to extend the analysis to 2030. Results The study found that Japan and the USA have the highest incidence and mortality rates for pancreatic cancer, with predicted ASIR values expected to exceed 15 per 100,000 in Japan by 2030. Mortality trends follow a similar pattern, with males consistently showing higher ASMR than females across all regions. China is expected to see continued growth in DALYs, particularly among males, while Korea exhibits stable or slightly declining trends. The longitudinal age curves indicate that pancreatic cancer rates rise significantly with age, especially in individuals over 65 years. By 2030, Japan and the USA are projected to experience the greatest increase in pancreatic cancer burden, while Korea’s trends remain relatively stable. Conclusions Pancreatic cancer continues to pose a significant public health challenge, particularly in aging populations. The predicted rise in incidence, mortality, and DALYs in Japan and the USA calls for urgent implementation of targeted screening and prevention strategies, particularly for older age groups and high-risk populations.